Utilization Of Household Organic Waste Into Solid/Liquid Compost And Tongue-In-Law Rope Fiber - Faizer, Maychel; Alfajri , Feriawan; Sucipto , Dovi Adi; Aldzikri, M. Iqbal; Afifudin, Rahmat; Prasetya, Andwini; Yulianti, Liza; Fariadi, Herri (Universitas Dehasen Bengkulu, 2025)
Household waste is often ignored and thrown away, even though waste can be utilized if managed as solid/water bokashi fertilizer and snake plant fiber. The purpose of community service is waste sorting, training activities for processing solid and liquid compost fertilizers using the solid and liquid bokashi method, and making raw materials for snake plant fiber crafts using the braiding method. The results of the activity were that the socialization participants were very enthusiastic about participating in the activity, especially after being given education through the provision of materials, distributing leaflets on making solid bokashi fertilizer and liquid organic fertilizer. The focus of the activity was on household waste management, so that residents of RT. 41 waste were able to independently manage and utilize snake plant leaves. The utilization of organic waste and the remains of pruning lush snake plant leaves can be processed into solid compost and liquid compost as well as snake plant fiber rope. The economic value of solid compost fertilizer is IDR 1,300.00 / kg, liquid fertilizer IDR 0 / L, and snake plant fiber rope is IDR 5,208.33 per 50 m.